2015
DOI: 10.1021/ac5038895
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Urinary 5-Hydroxymethylcytosine by Stable Isotope Dilution HPLC-MS/MS Analysis

Abstract: The sixth DNA base 5-hydroxymethylcytosine (5hmC) is the major oxidation product of the epigenetic modification 5-methylcytosine (5mC), mediating DNA demethylation in mammals. Reduced 5hmC levels are found to be linked with various tumors and neurological diseases; therefore, 5hmC is an emerging biomarker for disease diagnosis, treatment, and prognosis. Due to its advantages of being sterile, easily accessible in large volumes, and noninvasive to patients, urine is a favored diagnostic biofluid for 5hmC analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 53 publications
(105 reference statements)
2
92
0
2
Order By: Relevance
“…Discussion 5-hmC, as the hydroxylated form of 5-mC, was first discovered in T-even phage DNA in 1952 (15). A previous study indicated that 5-hmC was associated with diseases such as nerve disorders, leukemia and tumors (16). In recent years, 5-hmC has become more extensively studied.…”
Section: Low Level Of 5-hmc Was Correlated With Poor Prognosis Of Nsclcmentioning
confidence: 97%
“…Discussion 5-hmC, as the hydroxylated form of 5-mC, was first discovered in T-even phage DNA in 1952 (15). A previous study indicated that 5-hmC was associated with diseases such as nerve disorders, leukemia and tumors (16). In recent years, 5-hmC has become more extensively studied.…”
Section: Low Level Of 5-hmc Was Correlated With Poor Prognosis Of Nsclcmentioning
confidence: 97%
“…的准确定量. 此方法还可以提高DNA 5-甲基胞嘧啶 (5-methylcytosine, 5mC)的氧化产物分析的灵敏度, 包 括5-羟甲基胞嘧啶(5hmC)和5-醛基胞嘧啶(5fC) [73,74] .…”
Section: 液相色谱-质谱法unclassified
“…ESI-MS方法适用于5mC氧化产物5hmC和5fC的高灵 敏分析, 在此基础上, 结合SPE技术实现了健康人类尿 液中5mC初级氧化产物 5hmC 的检测 [74] . 与哺乳动物 methyladenine, 6mA), 其表观遗传功能也得到了系统 深入的研究 [90] .…”
Section: 灵敏的Uhplc-ms/ms方法检测人类精子的5mc甲基unclassified
“…Among them, salts, which can suppress ionization efficiency and contaminate ion source are present with high abundance [30]. In order to clean up salts and selectively enrich urinary ProdG adducts, C18 and HLB cartridges were used to obtain the optimized extraction.…”
Section: Optimization Of Solid-phase Extraction Protocolmentioning
confidence: 99%
“…Various methods have been developed for the detection of urinary nucleosides, including electrochemical method [18], immunoassays [19,20], capillary electrophoresis (CE) and high performance liquid chromatography (HPLC) [17,[21][22][23][24], matrixassisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) [25,26], liquid chromatography tandem mass spectrometry (LC-MS) [27][28][29][30][31][32]. In comparison to other methods, the LC-MS based methodologies take the advantages of high sensitivity and direct analysis with structural information from MS measurements [33].…”
Section: Introductionmentioning
confidence: 99%